Pengaruh Kompetensi Sumber Daya Manusia Dan Dukungan Sosial Terhadap Kinerja Pegawai Organisasi Perangkat Daerah (OPD) Kecamatan Penajam Kabupaten Penajam Paser Utara - Marliana Marliana; Nurmadhani Fitri Suyuthi; St. Rukaiyah (Journal of Management and Social Sciences, 2024)
In this research, quantitative methods were used to measure the influence of competency and social support on employee performance at the Regional Apparatus Organization (OPD) Office of Penajam District, North Penajam Paser Regency. This research aims to determine and analyze the impact of Human Resource Competency on Employee Performance. Second, this research aims to understand and analyze the Effect of Social Support on Employee Performance and third, this research also aims to evaluate the simultaneous impact of Human Resource Competency and Social Support on Employee Performance in Regional Apparatus Organizations (OPD) Penajam District, Penajam Regency North Paser. The research results show that employee competency has a positive and significant impact on their performance in the Penajam District OPD. This illustrates that the higher the level of competency, the more optimal the employee's performance, in line with the concept that skills and abilities directly influence work results. Additionally, social support also plays an important role, with the finding that support from colleagues and superiors creates a conducive work environment, increases motivation, and reduces stress levels, contributing to improved overall performance. Simultaneously, the combination of competence and social support also has a positive and significant impact on employee performance in the Penajam District OPD, emphasizing the importance of having adequate skills and social support in creating optimal conditions for improving performance.